Rencana Strategis Kesbangpol Kabupaten Solok: Analisis SWOT untuk Penguatan Kebijakan dan Program - Donly Wance Lubis; Syafwandi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to formulate a strategic plan for the National and Political Unity Agency (Kesbangpol) of Solok Regency using the SWOT analysis approach. A qualitative case study design was employed through in-depth interviews, stakeholder surveys, and policy document analysis. The findings reveal: (1) Strengths: competent human resources and strong collaborative networks; (2) Weaknesses: limited budget and insufficient supporting infrastructure; (3) Opportunities: increasing community participation and technological utilisation; (4) Threats: central policy instability and the potential for social conflict. The priority strategies include strengthening human resource capacity, optimising information technology, and innovating funding mechanisms. Policy recommendations highlight the importance of responsiveness to local dynamics and reinforcing impact-based evaluation systems.